The viticulture and wine production in the function of multifunctional and rural development of agriculture - Matić, Marko; Ivanković, Marko; Bunoza, Senka (Economics of Agriculture, 2010)
By using scientific methods applied in this scientific work such as: analytical method, quantitative analysis- costing calculation (the cost principal) and mathematical and statistical method (the dynamic analysis of trends),the authors have researched the economic efficiency and profitability of grape and wine varieties Žilavka and Blatina on the family estate in West Herzegovina. The research was conducted in the period 2006 – 2008 The results reached by the authors are following: The economy of grape Žilavka production quoted by the economy coeffcient was 1,12 in 2006 and 1,31 in 2008, and for Blatina 1,18 in 2006 and 1,34 in 2008. The production rentability of grape Žilavka quoted by the rentability coefficient was in the range of 12,03 % in 2006 up to 31,15 % in 2008, and for grape Blatina from 15,95 % in 2006 up to 25,66 % in 2008. The economy of wine Žilavka production quoted by the economy coeffcient was in the range of 1,41 in 2006 up to 1,47 in 2008, and for wine Blatina 1,42 in 2006 up to 1,47 in 2008. The rentability of wine Žilavka production quoted by the rentability coefficient was in the range of 29,06 % in 2006 up to 31,96 % in 2008, and for wine Blatina 29,81 % in 2006 up to 32,19 % in 2008.